Assessment of anemia and malnutrition among adolescent in Kalyan Karnataka region of Karnataka - Vijayshree Mathad; Shobha Badiger; Nitin Manjunath (Elsevier, 2023)
Introduction: Malnutrition and anemia among adolescents are a daunting problem throughout the world, but the most affected are the children from low socioeconomic strata and less developed regions. Hence, the present study was focused on assessing the prevalence of malnutrition and degree of anemia among adolescents in the Kalyan Karnataka region. Methodology: A sample size of 660 was considered. The study was carried out from April to August 2022 in schools selected based on the random number table among children aged 10 to 19 after obtaining baseline socio demographic profile. The investigations included assessment of Body Mass Index (BMI). Hemoglobin was estimated by the micro hematocrit method using a hemoglobinometer. The data was analysed using the Statistical Package for the Social Sciences (SPSS) 26 version. Results: The prevalence of anemia among adolescents in our study was 37.7%, and underweight was 36.1%. Adolescent females had a higher prevalence of anemia (44.5%). The mean age of the adolescents was 14 years. Underweight was more common among males as compared to females. The factors significantly associated with anemia were female gender, orphans, low socioeconomic strata, early onset of menstruation, and irregular menorrhagia in menstruating females. Conclusion: Anemia among female adolescents needs to be addressed by including iron-fortified foods and supplements in the school meal program, specifically among the children belonging to low socioeconomic strata in the Kalyan Karnataka region. A detailed longitudinal study needs to be carried out to assess the ill effects of anemia and the impact of preventive strategies among adolescents.